Improving Basic Services for the Bottom Forty Percent : Results of the Poverty and Social Impact Assessment of Decentralized Basic Service Delivery in Ethiopia - World Bank (Washington, DC, 2014)
This report is part of a programmatic knowledge series which will include future reports which will go further on the issues covered. These reports will include among others studies based on services delivery quality in health and education based on on-going surveys as well detailed survey based impact assessment the Promotion of Basic Services (PBS) program. This program based on multi-round surveys over the next three years, an impact assessment of the social accountability component of PBS program for which baseline survey has taken place and a full report is due in two years, all of these studies will further elucidate the findings in this report. This report is structured with a section describing the PBS program and inter-government fiscal transfers underlying Ethiopia's decentralized federal structure. That section will be followed by a section on study approach and then a section on the governance and accountability framework underlying the program. After that there will be a section on the effectiveness of Ethiopia's intergovernmental transfers program (IGFT) on development results in education, health and agriculture which will be followed by a section on the equity impact of the program focusing on income equity, gender equity, spatial equity and ethnic equity. That will be followed by conclusions and annexes including an annex on methodology.